Evolução contratual dos hospitais privados sob gestão da Secretaria Estadual de Saúde de Minas Gerais - Marisa Madureira (2020)
Introduction: The public-private partnerships is a format that is increasingly present in the health systems of several countries. There is a consensus in literature about the importance of private sector participation in BUHS (Brazilian Unified Health System). This participation should happen through the establishment of contractual instruments, but the informality in the relationship between public managers and private institutions is still a reality in Brazil. It notes that there was no development about contractual basis that formalize the public health sector's with private health services.In order to reduce informality in the provision of health services and make the process more effective, the Ministry of Health has resorted to some strategies, and in this sense the Policy for the Restructuring of Teaching Hospitals and the Philanthropic Hospitals Restructuring and Contracting Program were more successful, resulting in the contracting of all hospitals linked to the programs. However, hospitals linked to specific programs, the informality scenario persisted. Other strategies were tried until culminating in the publication of Law number 1.350 / 2018, which reaffirms as an act of improbity the transfer of resources to private entities without the prior conclusion of the contract, forcing states and cities to organize themselves to meet the legal precepts. In addition to ensuring the legality of transfers of financial resources, the contract shows the obligations and responsibilities of each of the parties and is an important mechanism for the management, control and evaluation of the contracted services. Objective: To analyze the contractual evolution of private hospitals under the management of the Secretariat Health State of Minas Gerais, legitimizing the relationship between the public manager and private providers. Method: It presents the typology of the existing contracts and establishes a comparison of the performance of the set of contracted hospitals with hospitals without a contract with regard to the volume of production and the occupancy rate of general beds in intensive care units. Results: Data collection in a single instrument in order to provide quality information to guide managers towards efficient hiring.